Needs of integrated science textbook for junior high school based on learning style (descriptive research) - G Priscylio; D Rochintaniawati; S Anwar (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
One of the factors that determine the achievement of learning objectives is theteaching materials used in the learning. Teaching Materials are all materials (information, tools, and text) thatare arranged systemetically, which display the whole competencies to be mastered by students [1]. One of the teaching materials that are often used is teaching materials in the form of textbook. Textbooks are typically the main source of learning material for students and the source of information on a specific subject or field [2]. This research is a Descriptive Research that aims to see the urgency of teaching materials in the form of textbooks in integrated science lesson junior high school related to visual student learning style. This research was conducted at Junior High School 29 of Bandung. The data collection instrument used in this research is in the form of teacher and students questionnaire. The answers of teachers and students questionnaire wasanalyzed descriptively for each item. The results of the questionnaire showed that both teacher and Students prefer textbooks that use more attractive colours, more detailed explanations and more examples related to daily life. The finding of the research suggest that textbook is urgently needed to support learning process mostly for visual learning style.